Presenteeism in Cigarette Workers in the Light of Job Insecurity and Job Demands - Meilala, Putri Amanda; Trubus Raharjo (RUBINSTEIN, 2026)
This study aims to examine the relationship between job insecurity, job demands, and presenteeism among cigarette factory workers. Presenteeism refers to employees’ tendency to remain physically present at work despite experiencing physical or psychological health problems that may reduce work effectiveness. This study employed a quantitative correlational design involving cigarette factory workers selected through accidental sampling. Data were collected using three validated measurement scales, namely the presenteeism scale, job insecurity scale, and job demands scale. The data were analyzed using Pearson correlation and two-predictor regression analysis. The results showed a significant positive relationship between job insecurity, job demands, and presenteeism, with a correlation coefficient of 0.647 and a significance level of p < 0.01. Job insecurity and job demands jointly contributed 41.8% to presenteeism. Further analysis indicated that job insecurity had a positive relationship with presenteeism (r = 0.629; p < 0.01), while job demands were also positively associated with presenteeism (r = 0.546; p < 0.01). These findings indicate that workers who experience higher job insecurity and greater job demands are more likely to continue working despite being in poor physical or psychological condition. Practically, the results suggest that organizations need to reduce excessive job demands, improve perceived job security, and strengthen employee well-being policies to minimize presenteeism and maintain workplace productivity.